SOCIOLOGICAL ANALYSIS OF CYBER AND NON-CYBER RELATED CRIMINAL BEHAVIOURS AMONG UNDERGRADUATES IN IMO STATE’S TERTIARY INSTITUTIONS - Ijeoma Chidiezie-Chineke, Julie (African Journal of Social and Behavioural Sciences, 2024)
The study was on the sociological analyses of cyber and non-cyber-related criminal behaviours among undergraduates in tertiary institutions in Imo State. The study was a survey adopting a correlational research design. Three research questions were posed for the study. The target population of the study was 55,000 undergraduates. The study sample was 598 students based on the data of students of tertiary Institutions in Imo State of Nigeria in the custody of central Police station Owerri. A pro forma titled: Criminal Behaviour as Related to Demography profiles of undergraduates in tertiary institutions of Imo State between 2013 and 2019 was used. The research questions were answered using mean scores and percentage ratings. Findings showed, among others, that cultism is the most common criminal behaviour among undergraduates. Children from families with high social backgrounds families mostly indulge in cyber and non-cyber-related criminal behaviours. It was then recommended, among others, that the government, through the Ministry of Education, should carry out serious awareness programmes on the dangers associated with cultism among undergraduates. Parents with high social backgrounds should create time to monitor the activities of their children and always admonish them when they try to go astray. It has been recommended that these tertiary institutions in Imo State and other parts of the country should accelerate campaigns targeted at cybercrime awareness among their students. This is from the vantage point of making them understand that cybercrime is a criminal offence punishable under the Nigerian criminal act with the attendant adverse consequence of jeopardizing their educational career if they are caught and convicted.